Seed Health and Quality of Rice Seeds Produced by Farmer and Growing in Cho Moi District, An Giang Province, Vietnam - Duong Huong Vo Thi; Cho Anh Huynh; Toan Thanh Le; Sang Vinh Tran; Tu Thi Ngoc Phan (Universitas Andalas, 2019)
This study was conducted at Laboratory in An Giang University; the varieties examined were collected from farmer households in 2018 – they were varieties that the farmer stored for the next crop (Winter-Spring) from Autumn-Winter crop in Cho Moi district, An Giang Province, Vietnam. The research evaluated the quality of seed rice, which is provided and planted by the farmer. As a result, this study showed that almost all of the varieties of seed rice from farmer households indicated the ratio of filled-grain, the germination, and the determination of seedling healthy, which are lower than certified variation. Besides, the samples of seed rice from farmer household have more infected fungal; especially the samples with higher in a filled-grain ratio is less infected by fungi, there were 12 types of seed borne-fungi in rice varieties from the farmer (in Cho Moi district), included: Alternaria padwickii, Rhizoctonia solani, Aspergillus oryzae, Bipolaris oryzae, Cercospora janseana, Curvularia lunata, Fusarium moniliforme, Pyricularia oryzae, Sarocladium oryzae, Tilletia barclayana, Fusarium graminearum, and Ustilaginoidea virens